Open Reduction and Internal Fixation of the Isolated Tibial Lateral Plateau Posterior Fracture Using Direct Posterior Split Gastrocnemius Approach - Guzelali Ozdemir; Baris Yilmaz; Ahmet Oztermeli (Case Reports in Surgery)
Open reduction and internal fixation of the isolated tibial lateral plateau posterior fractures using direct posterior split gastrocnemius approach is a safe and effective method.